Perforin-2 is dispensable for host defense against Aspergillus fumigatus and Candida albicans - Mariano A. Aufiero; Li-Yin Hung; De'Broski R. Herbert; Tobias M. Hohl (mSphere)
ABSTRACT Myeloid phagocytes are essential for antifungal immunity against pulmonary Aspergillus fumigatus and systemic Candida albicans infections. However, the molecular mechanisms underlying fungal clearance by phagocytes remain incompletely understood. In this study, we investigated the role of Perforin-2 (Mpeg1) in antifungal immunity. We found that Mpeg1−/− mice generated on a mixed C57BL/6J-DBA/2 background exhibited enhanced survival, reduced lung fungal burden, and greater neutrophil fungal killing activity compared to wild-type C57BL/6J (B6) mice, suggesting that Perforin-2 may impair antifungal immune responses. However, when we compared Mpeg1−/− mice with co-housed Mpeg+/+ littermate controls, these differences were no longer observed, indicating that initial findings were likely influenced by differences in the murine genetic background or the microbiota composition. Furthermore, Perforin-2 was dispensable for antifungal immunity during C. albicans bloodstream infection. These results suggest that Perforin-2 is not essential for host defense against fungal infections in otherwise immune-competent mice.IMPORTANCEHumans encounter fungal pathogens daily and rely on innate immune cells to clear Aspergillus fumigatus, the leading cause of mold pneumonia worldwide, and Candida albicans, the most common cause of fungal bloodstream infections. The World Health Organization has classified A. fumigatus and C. albicans as critical priority fungal pathogens due to the emergence of drug resistance and the increasing number of susceptible individuals across the globe. The mechanisms by which innate immune cells clear these fungal pathogens remain incompletely defined. In this study, we examined the role of a pore-forming protein called Perforin-2 in host defense against these fungal pathogens, in part because Perforin-2 has been implicated in antibacterial host defense. Our findings reveal that Perforin-2 is dispensable for antifungal immunity against respiratory A. fumigatus and systemic C. albicans infections in mice, suggesting that the antimicrobial activity of Perforin-2 does not extend to these two fungal pathogens.